Taiwanese species of the ant genus Technomyrmex (Formicidae: Dolichoderinae) - Yamane, Seiki; Leong, Chi-Man; Lin, Chung-Chi (Zootaxa, 2018)
The Taiwanese species of the ant genus Technomyrmex are revised with recently collected material. Five species are recognised, three in the T. albipes species group and two in the T. bicolor species group, including one new species, T. formosensis sp. nov., and two newly recorded species. The occurrence of T. albipes, previous records of which were based on misidentifications, is confirmed for the first time in Taiwan. The structure of genitalia is compared between winged and wingless males of T. brunneus.